2015
DOI: 10.3892/ol.2015.3299
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the novel heat shock protein 90 inhibitor AUY922 in renal cell carcinoma ACHN and 786-O cells

Abstract: Abstract. The aim of the present study was to investigate the effects of the heat shock protein (HSP)90 inhibitor AUY922 on the proliferation and migratory ability of renal cell carcinoma (RCC) cells. The expression of HSP90 was measured in vitro using western blotting and quantitative polymerase chain reaction in the ACHN and 786-O cell RCC lines, and also in the immortalized normal human proximal tubule epithelium HK-2 cell line. The effects of the time and concentration of AUY922 administration were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Renal cell carcinoma, a lethal urologic malignancy that originates in renal tubular epithelial cells, comprises approximately 90% of all kidney cancers and accounts for 2-3% of all cancers worldwide [ 46 , 47 ]; lung cancer is the second most common type of cancer worldwide, with approximately 1.6 million new cases diagnosed each year, and the leading cause of cancer-related death, estimated at 1.37 million annually [ 48 , 49 ]. Radiotherapy is a crucial component of treatment for these and most other types of cancer, and treatments that increase radiosensitivity in resistant tumor cells would help improve the efficacy of radiotherapy [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Renal cell carcinoma, a lethal urologic malignancy that originates in renal tubular epithelial cells, comprises approximately 90% of all kidney cancers and accounts for 2-3% of all cancers worldwide [ 46 , 47 ]; lung cancer is the second most common type of cancer worldwide, with approximately 1.6 million new cases diagnosed each year, and the leading cause of cancer-related death, estimated at 1.37 million annually [ 48 , 49 ]. Radiotherapy is a crucial component of treatment for these and most other types of cancer, and treatments that increase radiosensitivity in resistant tumor cells would help improve the efficacy of radiotherapy [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…HSP90 makes the mutated oncoproteins able to avoid misfolding and degradation and permits the malignant transformation (Barrott & Haystead, 2013; Wu et al, 2017). HSP90 promotes the growth and inhibits apoptosis in multiple types of cancers, such as bladder carcinoma (Lebret et al, 2003), medulloblastoma (Alexiou et al, 2013), renal (Zhu, Zhu, Qi, & Qiu, 2015), lung (Esfahani & Cohen, 2016), colorectal (Moser et al, 2007), and acute leukemia (Tian et al, 2014) as well as HCC (Dong, Xue, et al, 2018; C. Wang, Zhang, et al, 2016). More recently, it was shown that the HSP90 is a potential biomarker of HCC, and the diagnostic value of its expression for HCC detection was reported (Wei et al, 2020).…”
Section: Introductionmentioning
confidence: 99%